Comparison of blood clam (anadara granosa) shell paste, shrimp (litopenaeus vannamei) shell paste and casein phosphopeptide-amorphus calcium phosphate (CPP-ACP) paste as teeth remineralization material - Asmawati Asmawati; Bahruddin Thalib; Alqarama M. Thalib; Delvi S. Reni; Rafikah Hasyim (DiscoverSys Inc., 2018)
Objective: The aim of this study was to determine the comparison of blood clam (anadara granosa) shell paste, shrimp (litopenaeus vannamei) shell paste and casein phosphopeptideamorphus calcium phosphate (CPP-ACP) paste as teeth remineralization material.Material and Methods: This study was an experimental laboratory with cross sectional design. Study sample was 15 maxillary central incisors that were applied with 35% hydrogen peroxide for 2 hours, then assessed with Energy Dispersive Spectroscopy (EDS). Samples were divided into 3 groups: 5 samples were applied using blood clam (anadara granosa) shell paste, 5 samples using shrimp shell paste and 5 samples were applied using CPP-ACP paste every 8 hours for 14 consecutive days then checked with EDS. Data analysis using SPSS test independent t-test to see comparison of blood clam (anadara granosa) shell paste, shrimp (litopenaeus vannamei) shell paste and casein phosphopeptide-amorphus calcium phosphate (CPP-ACP) paste as teeth remineralization material.Results: The result of this study showed P> 0.05 which means there was no significant difference between blood clam shell paste, shrimp shell paste and CPP-ACP mineral composition.Conclusion: Blood clam shell paste and shrimp shell paste has an effective value to be used as tooth remineralization material.